Studies on Gracilaria changii (Gracilariales, Rhodophyta) from Malaysian mangroves - Phang, Siew Moi; Shaharuddin, Shafeei; Noraishah, Hashim; Sasekumar, A. (Kluwer (now part of Springer), 1996)
Gracilaria changii, recorded from Malaysia and Thailand, is one of the more abundant agarophytic seaweeds found in Malaysia. A wild population of Gracilaria changii growing in mangroves was monitored for seasonal variation in agar content and gel strength as well as spore production. Agar yield and gel strength ranged from 12 to 25% dry weight and 294 to 563 g cm−2, respectively, over a 15-month period. Gel strength but not yield was positively correlated with amount of rainfall. Cystocarps were observed throughout the study, but use of sporetraps showed that spore release peaked around July–August and January–February after the two monsoon periods.